Pengaruh Intellectual Capital dan Corporate Social Responsibility Terhadap Return on Assets Dimoderasi Ukuran Perusahaan - Cahyani, Riska Dwi; Tannar, Oryza (Al-Buhuts, 2024)
Companies listed in the fast-moving consumer goods category tend to have stable operational activities. In the competitive business world, companies must be able to optimize all the resources they possess, both tangible and intangible. Additionally, companies have social responsibilities towards their surrounding environments. This research aims to determine the influence of intellectual capital and corporate social responsibility on financial performance, projected by return on assets, and moderated by company size. The research population consists of companies listed in the fast-moving consumer goods category on the Indonesia Stock Exchange. This study uses a quantitative method. The sampling method employed in this research is purposive sampling, and the data collection technique used is documentation. The testing tool used in this research is the Software Partial Least Square (PLS) 3.0. The results of this study indicate that the first independent variable, intellectual capital, affects financial performance. Additionally, the second independent variable, corporate social responsibility, also affects financial performance. However, the moderating variable, company size, does not strengthen the influence of intellectual capital and corporate social responsibility on financial performance.